2014
DOI: 10.2319/050914-335.1
|View full text |Cite
|
Sign up to set email alerts
|

Metal ion release from silver soldering and laser welding caused by different types of mouthwash

Abstract: Objective: To compare metal ion release from samples welded with silver soldering and laser welding when immersed into mouthwashes with different ingredients. Materials and Methods: A total of 72 samples were prepared: 36 laser welded and 36 silver soldered. Four samples were chosen from each subgroup to study the morphologic changes on their surfaces via scanning electron microscopy (SEM). Each group was further divided into four groups where the samples were submerged into mouthwash containing sodium fluorid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
(45 reference statements)
4
14
0
Order By: Relevance
“…Previous studies comparing silver solder and laser welding showed more metal ion release for soldering [16,22,40]. In this study, Zn, Ag, and Cd ions showed no difference in variation along the periods among the groups, concluding that there was no significant increase in the release of these ions when comparing the groups.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Previous studies comparing silver solder and laser welding showed more metal ion release for soldering [16,22,40]. In this study, Zn, Ag, and Cd ions showed no difference in variation along the periods among the groups, concluding that there was no significant increase in the release of these ions when comparing the groups.…”
Section: Discussionsupporting
confidence: 47%
“…In group 4, for Ni ions, there was a statistic difference from T4 to T1 (P = 0.001), T4 to T2 (P = 0.017), and T4 to T3 (P = 0.001), indicating that TIG-welded appliances had greater Ni ion release and that this increase in ions did not regress during the assessed period. The level of metal ion release from samples of silver soldering was higher than from samples of laser welding in a previous study [22], with greater amounts of Ni, Cr, and Fe released from silver soldering by different types of mouthwash [22]. Whereas the methods of the experiments vary, the results differ, and the comparison is difficult to be made.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Listerine is an alcohol-based mouthwash. In this regard, Erdogana 21 studied the metal ion release from silver soldering and laser welding caused by different types of mouthwash and reported that NaF+alcohol (Listerine) mouthwashes exhibited the highest amount of metal ion release.…”
Section: Discussionmentioning
confidence: 99%
“…Higher release of titanium in nitride‐ and rhodium‐coated alloys in Listerine may be because this antiseptic contains the highest concentration of hydrofluoric acid causing the damage of the surface layer. Additional release of metal ions above saliva after exposure to oral antiseptics is reported earlier, higher in those based on alcohol and fluorides than chlorhexidine, and least in aqueous solutions of herbal extracts . Ion release could be also related to microstructure of the alloy .…”
Section: Resultsmentioning
confidence: 77%